2011
DOI: 10.1002/app.34192
|View full text |Cite
|
Sign up to set email alerts
|

Development of porous lamellar chitosan‐alginate membranes: Effect of different surfactants on biomaterial properties

Abstract: In this work, porous lamellar chitosan-alginate membranes were developed without the use of freeze-drying methods or other vacuum-based approaches. The effects of two different surfactants, Tween 80 and Pluronic F68, on the properties of the membranes were evaluated, aiming at the production of stable consistent foams with improved polysaccharide dispersion. The membranes prepared with Tween 80 had a tensile strength around 1.5 MPa, elongation at break of 2.1% and liquid uptake from 590 to 1370% in distinct so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(19 citation statements)
references
References 67 publications
2
16
0
1
Order By: Relevance
“…Although the porosity was not calculated, both membranes were porous, and the membrane treated with Pluronic F68 displayed a higher porosity than the one treated with Tween 80. The membranes treated with either Pluronic F68 or Tween 80 displayed no zone of inhibition against Pseudomonas aeruginosa and Staphylococcus aureus [106]. This implies that the membranes did not possess any antibacterial properties, therefore an antibacterial drug may be introduced to the membranes.…”
Section: Ionic Gelation Technique Employed In Fabrication Of Chitosanmentioning
confidence: 97%
See 1 more Smart Citation
“…Although the porosity was not calculated, both membranes were porous, and the membrane treated with Pluronic F68 displayed a higher porosity than the one treated with Tween 80. The membranes treated with either Pluronic F68 or Tween 80 displayed no zone of inhibition against Pseudomonas aeruginosa and Staphylococcus aureus [106]. This implies that the membranes did not possess any antibacterial properties, therefore an antibacterial drug may be introduced to the membranes.…”
Section: Ionic Gelation Technique Employed In Fabrication Of Chitosanmentioning
confidence: 97%
“…The membrane treated with Tween 80 had the highest tensile strength of about 1.5 MPa, elongation at break of 2.1%, fluid uptake from 590 to 1370%, and the membrane increased in thickness up to 3.9 times when immersed in water [106]. The membranes treated with Pluronic F68 had a tensile strength of 1 MPa, elongation at break of 2%, fluid uptake from 774 to 1380%, and displayed increased thickness of about 3.2 times after exposure to water [106]. The tensile strength of both membranes was too high for wound dressing applications; however, the fluid uptake was still in the acceptable range.…”
Section: Ionic Gelation Technique Employed In Fabrication Of Chitosanmentioning
confidence: 99%
“…fabricated ciprofloxacin‐loaded alginate/chitosan sponges and established that the obtained product could be used as a very promising alternative wound dressing to use in wound/burn dressing applications and wound healing studies. Zorzi Bueno and Maria Moraes are reported that chitosan/alginate composite films can be used as appropriate wound dressings or scaffolds in the tissue engineering field. The adhesive nature of chitosan, arising from the cationic structure, promotes cell adhesion due to the electrostatic interaction with anionic glycosaminoglycan and proteoglycans, which have substantial contributions in growth differentiation and migration process of fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…Also, it provides an accelerated skin regeneration by increasing natural hyaluronic acid formation at the wound area as a result of N ‐acetyl‐β‐ d ‐glucosamine releasing during the depolymerization. These characteristics make it a perfect biopolymer for the promising biomedical applications …”
Section: Introductionmentioning
confidence: 99%
“…In the present work, the PVA/CS blended membranes were prepared with different CS loadings at fixed total polymer content. CS is one of the most abundant biopolymer in nature and is N‐deacetylated derivatives of chitin which naturally exists in some creatures such as insects and marine crustaceans . High number of reactive amino and hydroxyl groups along with high mechanical strength and good film‐forming ability make CS a promising candidate as the second hydrophilic polymer to form a blend with PVA.…”
Section: Introductionmentioning
confidence: 99%